If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 2E + -5x + 1 Reorder the terms: y = 1 + 2E + -5x Solving y = 1 + 2E + -5x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 1 + 2E + -5x
| 0=-16t^2+0t+36 | | 3-(-2m)+9-m= | | 2+x(x+2)-3=x^2+2x+1-4 | | 2t*-7t=12 | | y=-1.45x+71.5 | | tg(x)+tg(3x)+sin(2x)=0 | | 6a-48=6(a-1) | | log(2)0=0 | | y^2+11y+45=0 | | x*-5x+10=0 | | 5m+7=4m+9 | | an=3*2n-1 | | (2x^2)/(4x) | | y=log(3*(x^2)-9)/x^2-5x | | (3x-7)=-15x+35 | | CosA=0.35 | | 3x+12=5x+9+1 | | 20+20+20= | | 8x-(-4x+9)= | | 27x=9x+3 | | msquared=16 | | 6(x-2)+8x(x-2)=0 | | 2+5=-3 | | 2x/3-3x/8=7/12 | | 4x^2/8y^3 | | log(x)(8)=6 | | 3x+2x+10=940+x-4 | | 2x+3x+2=604+x+6 | | 12x+12=x+15 | | 28a^2b^4c^5-42a^3b^2c^4+56ab^3c^3= | | 7x-(3x-2)=-10 | | 5x-2+4x+10=640+6x-20 |